Application of fuzzy logic for controlling mechanism of relative manipulation robot (MRM robot) - Khoi, Phan Bui; Toan, Nguyen Van (Vietnam Journal of Science and Technology, 2016)
In robot control, mathematical equations describing dynamic behaviors of robots are usually complicated. Additionally, the components such as inertial and friction parameters appearing in these equations are very difficult to determine exactly. With robots having complex structure such as parallel robots, MRM robots etc., the derivation of dynamic equations becomes more difficult and sometimes cannot obtain analytically. In those cases, controlling robot based on its equations of motion is quite hard. Applying fuzzy logic for robot control can overcome the mentioned drawbacks. This is because fuzzy control algorithm gives favorable condition to deal with the lack of adequation as well as inaccuracy of components in robot’s dynamic equations. Furthermore, the fuzzy rules are created by clauses which based on human logic, so it is easily to understand and implement. This paper discusses the application of fuzzy logic for controlling MRM robots. To compare the results obtained from fuzzy control, this paper are also adressed the use of the computed torque algorithm to control MRM robots